Numeracy Literacy and Quantitative Literacy in Biology Education: A Systematic Literature Review - Miftahul Jannah; Eni Nuraeni; Mimin Nurjhani Kusumastuti; Fumitoshi Murae; Indriyani Rachman (Universitas Syiah Kuala, 2026)
The quality of education in the 21st century demands competencies beyond conceptual knowledge, including numeracy and quantitative literacy. However, students in Indonesia continue to demonstrate low achievement in these skills, as reflected in the 2022 Programme for International Student Assessment (PISA) results. This study aims to systematically review the development, trends, and contributions of numeracy and quantitative literacy research in biology education. The study was conducted using the systematic literature review (SLR) method with a preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach covering articles published between 2014 and 2025. A total of 14 Scopus-indexed articles were selected based on inclusion and exclusion criteria. The results of the study show an increasing trend in publications since 2023, in line with the strengthening of global literacy policies such as sustainable development goals (SDGs) 4.6 and the 2022 PISA assessment. The majority of studies used a quantitative approach (57%) and were conducted in the United States (43%) and Indonesia (36%), with the greatest focus on ecology and evolution (29%) and undergraduate education (57%). Learning activities that support the improvement of numeracy and quantitative literacy include four main classifications, namely the integration of contextual questions, practicums and experiments, digital media, and project-based learning and quantitative modeling. This study also identified a research gap, namely the absence of studies that directly apply Kit learning media and the science, technology, engineering, and mathematics (STEM) approach in the context of numeracy and quantitative literacy in environmental change material. These findings provide a basis for developing innovative learning strategies to strengthen 21st-century competencies